Data-driven analysis in building energy consumption - Poh, Shih Gee (Nanyang Technological University, 2022)
In a global effort focusing on driving sustainability, the building sector has been widely recognised to have the most potential in reducing building energy consumption and greenhouse gas emission. Technology advancement in the building sector ensures that building data tracking is available, which allows people to study the relationship and characteristics of variables that would ultimately impact a building’s energy consumption. Therefore, it is essential to provide an accurate and efficient means to analyse such data to allow for an accurate representation of building energy consumption.